Hantu PKI dan Ujung Rekonsiliasi (Analisis Framing Pemberitaan PKI Era Presiden Abdurrahman Wahid dan Joko Widodo pada Majalah Tempo dan Gatra) - Meigitaria Sanita; Puji Rianto (Jurnal Komunikasi, 2018)
The issue of PKI and the efforts of reconciliation rose by mass media every year become a controversial issue. This issue increased especially in the era of President Abdurrahman Wahid (Gus Dur) and Joko Widodo. This research explains how Tempo and Gatra constructed PKI and framed the reconciliation issues in this two presidency era. This research uses Robert Entman’s model of framing analysis. The research found that articles in Tempo tend to place the PKI as a victim, support reconciliation efforts, and the importance of historical alignment. According to Tempo, the New Order had a major role in "shaking up" the PKI. Gatra, on the other hand, tends to be balanced and views the history of the PKI as historical traumatic for Indonesian peoples. Gatra supports reconciliation done naturally, and that history should be reexamined. The difference between the two magazines was influenced by ideology, organizational routine, and extra media power. Keywords: PKI, Framing Analysis, Construction, Reconsiliatio